FACEBOOK STATUSES AND CONSTRUCTION OF USERS’ SOCIAL IDENTITIES - D Darmanto; Ahmad Zuhri Rasyidi; Abdul Rahim (LPPM Institut Pendidikan Nusantara Global, 2022)
This study was focused on investagating and analyzing the users' social identities (ethnicity and gender) on Facebook statuses. This study was conducted at describing the Facebook statuses construct users' ethnicity and the Facebook statuses contruct users' gender. The design of this study utilized a descriptive qualitative. The subject of this research was the Facebook users who are friends of the present researcher on Facebook. In collecting the data, the present researcher undertook the following procedures: observation and documentation. The results of the study showed that the Facebook users' ethnicity can be seen from the Facebook statuses. On the other hand, the Facebook users' gender cannot be seen from the Facebook Statuses.